New and Simple Endo-extra Oesophagotracheal Method of Developing the Fistula for the Implantation of a Voice Prosthesis. Issue 3 (1997) - Lichtenberger, G.
Abstract : The author has simplified the Blom-Singer 1 puncture. The fistula is formed with the help of his new device, the endo-extralaryngeal needle carrier and pointed metal cone fixed to a catheter. The voice prosthesis is placed in the fistula formed thus in an endo-extra oesophagotracheal way. The advantage of the method is, that when the fistula being formed from inside out, the back wall of the oesophagus will not become injured.